Minimal Architecture Lithium Batteries: Toward High Energy Density Storage Solutions. Issue 16 (18th January 2023) - Celè, Jacopo; Franger, Sylvain; Lamy, Yann; Oukassi, Sami
Abstract: The coupling of thick and dense cathodes with anode‐free lithium metal configuration is a promising path to enable the next generation of high energy density solid‐state batteries. In this work, LiCoO2 (30 µm)/LiPON/Ti is considered as a model system to study the correlation between fundamental electrode properties and cell electrochemical performance, and a physical model is proposed to understand the governing phenomena. The first cycle loss is demonstrated to be constant and independent of both cathode thickness and anode configuration, and only ascribed to the diffusion coefficient's abrupt fall at high lithium contents. Subsequent cycles achieve close to 100% coulombic efficiency. The examination of the effect of cathode thickness demonstrate a nearly linear correlation with areal specific capacity for sub‐100 µm LiCoO2 and 0.1 mA cm −2 current density. These findings bring new insights to better understand the energy density limiting factors and to suggest potential optimization approaches. Abstract : Battery capacity as a function of LiCoO2 cathode thickness is studied. A comprehensive physical model is developed to investigate the first cycle loss and the subsequent cycling. All‐solid‐state, anode‐free micro‐batteries, with cathode ranging from 5 to 30 µm, are tested to tune the model and demonstrate its applicability. Finally, projected performances of above 100 µm thick cathode are presented.